Effect of Nutrient Sources on Productivity of Spring Maize (Zea Mays L.) at Khairahani, Chitwan, Nepal - Yadav, Rajesh; Dahal, Khem Raj; Adhikari, Bishnu Bilas; Ghimire, Prakash; Belbase, Narayan Prasad (Multi-Disciplinary Explorations: The Kasthamandap College Journal, 2024)
Maize is second most important crop of Nepal grown mostly for food, feed and fodder. While many biotic and abiotic factors may lead to yield gaps in maize, soil fertility degradation and poor nutrient management are major factors in low productivity. A research study entitled “Effect of nutrient sources on productivity of spring maize at Khairahani, Chitwan, Nepal” was conducted in Agronomy farm of Rampur Campus, Khairahani Chitwan Nepal during the spring season, 2021 to identify the appropriate nutrient source for the maximum growth and yield of maize (Zea mays L), variety Arun-2. The experiment was laid out in Randomized Complete Block Design with eight different source of nutrients as treatments viz: i). Vermicompost (4.8 tonne/ha) ii). Goat manure (8 tonne/ha) iii). Bio-compost (wonder 2.4 tonne/ha) iv). Compost (24 tonne/ha) v). FYM (24 tonne/ha) vi). Poultry manure (4 tonne/ha) vii). NPK 120:60:40 Kg/ha as chemical fertilizer and viii). Control replicated thrice. The results showed that nutrient sources significantly influenced the growth and yield of maize. The highest yield (7.17 tonne/ha) and 1000 seed weight (439 g) was found in the treatment with poultry manure used at the rate of 4 tonne/ha. Significantly, higher number of leaves per plant, leaf area index, stem length, fresh weight and dry weight were found higher in FYM (24 tonne/ha). Similarly, significantly higher harvest index% (32) was recorded in the plots treated with poultry manure. Among the treatments, poultry manure seemed to be economically better for yield of spring maize among different organic manures with higher B/C ratio (2.55) in the plain subtropical areas of Chitwan.